Risk factors for coronary artery disease and acute coronary syndrome in patients ≤40 years old. (September 2016) - Alkhawam, Hassan; Sogomonian, Robert; El-Hunjul, Mohammed; Kabach, Mohamad; Syed, Umer; Vyas, Neil; Ahmad, Sumair; Vittorio, Timothy J
Objective: In this study, we assessed the risk factor profile in premature coronary artery disease (CAD) and acute coronary syndrome for adults ≤40 years old.Methods: A retrospective chart analysis of 397 patients ≤40 years old admitted from 2005 to 2014 for chest pain and who underwent coronary arteriography.Results: Of 397 patients that had undergone coronary arteriography, 54% had CAD while 46% had normal coronary arteries. When compared with patients with normal coronary arteries, patients with CAD were more likely to smoke tobacco, have dyslipidemia, be diabetic, have BMI >30 kg/m 2, have a family history of premature CAD and be male in gender.Conclusion: Healthcare intervention in the general population through screening, counseling and education regarding the risk factors is warranted to reduce premature CAD.